Substrates in the development of a sports turfgrass Tifton 419 - Ferreira dos Santos, Patrick Luan [UNESP]; Monteiro de Castilho, Regina Maria [UNESP] (Soc Brasileira Floricultura & Plantas Ornamentais, 2018)
Bermuda grass are the most widely used today in high performance sports fields, the cultivar Tifton 419 is widely indicated for installation in these areas, however, there is no official a recommendation in the literature of the best substrate for the implantation of this species, and research is needed to meet this demand. In this way, the objective of this study was to evaluate the influence of substrates in the development of the Tifton 419 sporting lawn. The experiment was conducted in field with grass carpets implanted in black plastic containers (volume 8.46 L), in a completely randomized design with five substrates and 12 replicates, with treatments: soil (100%), medium sand (100%), soil (50%) + medium sand (50%), soil (33%) + medium sand (33%) + organic compost (33%) and medium sand (50%) + organic compost (50%). Macro and microporosity, total porosity, density, chlorophyll content (a + b) and fresh and dry leaf mass were evaluated. The results showed that there was influence of the substrate on the development of the turfgrass, with the medium sand (50%) + organic compost (50%) presenting greater increases of fresh and dry mass (1.09 and 0.44 kg m-2), which may lead to higher maintenance costs of the cut, and soil (33%) + medium sand (33%) + organic compost (33%) presented good results of the analyzes performed, being the one recommended for the development of the cultivar Tifton 419 in sports fields.
Keywords: Cynodon spp.; bermuda grass; organic compost; physical properties